Periodontitis and type II diabetes: a two‐way relationship. Issue 4 (December 2013) - Chee, Brian; Park, Boram; Bartold, P Mark
Abstract For many years an association between diabetes and periodontitis has been suspected. In more recent times this relationship has been suggested to be bidirectional with each condition being able to influence the other. In this review the two‐way relationship between diabetes and periodontitis is considered. For this narrative review a very broad search strategy of the literature was developed using both EMBASE and MEDLINE (via PubMed) databases. The reference lists from the selected papers were also scanned, and this provided an additional source of papers for inclusion and further assessment. The data available suggest that diabetes is a risk as well as a modifying factor for periodontitis. Individuals with diabetes are more likely to have periodontitis and with increased severity when diabetes is uncontrolled/poorly controlled. Possible mechanisms of how diabetes affects periodontitis include adipokine‐mediated inflammation, neutrophil dysfunction, uncoupling of bone and advanced glycation end‐products–receptor for advanced glycation end‐products interaction. Evidence is accruing to support how periodontitis can affect diabetes and complications associated with diabetes. There is some evidence demonstrating that periodontal therapy can result in a moderate improvement in glycaemic control. Available evidence indicates that diabetes and peridontitis are intricately interrelated and that each condition has the capacity to influence clinical features of each other.